Translational agriculture: Data and knowledge needs to accelerate innovation and impact - Koo, Jawoo (2016)
IFPRI Research Fellow Jawoo Koo’s presentation at the third Global Conference on Agricultural Research for Development (GCARD3). For more information, please visit: https://www.ifpri.org/event/third-global-conference-agricultural-research-development